Should Lima airport concessionaire be allowed to obtain monopolistic rents by charging foreigners a transfer fee? - Defilippi, Enzo (2023)
Jorge Chavez International Airport (JCIA) is Peru’s main airport, handling 95% of the country’s international traffic. Since its concession in 2001 international transfers have grown 15 times and in 2019 represented 42% of the international outbound traffic. This substantial increase, and the fact that transfer passengers do not pay a fee for the use of the airport’s infrastructure, suggest a misalignment between the incentives faced by concessionaire and the public interest. This misalignment has the potential of reducing the Peru’s air connectivity in the future. The goal of this paper is to assess: (i) if it is convenient to authorize the JCIA’s concessionaire to charge a transfer fee to foreign nationals even though this might generate economic rents, and (ii) if so, whether this fee should be set by the market or by the regulator. Results suggest that it would be desirable to allow the concessionaire to charge a transfer fee even if this results in economic rents, and that JCIA faces competition within the geographic market of international transfer services, which implies that if fee is authorized it should not be set by the regulator.